The Criminal Responsibility for Abuse of Authority in Blocking Online Gambling Based on Indonesian Cyber Law - Muhammad Ridwan Lubis; Cut Nurita; Rini Novita (Unissula, 2026)
Online gambling in Indonesia has developed into a complex cybercrime involving not only players, operators, promoters, and site administrators, but also officials who control access-blocking systems. This study aims to examine criminal law regulation of online gambling involving state officials, analyze their criminal liability for abuse of blocking authority, and formulate a supervision and law enforcement model for protecting Indonesia’s digital space. This study uses doctrinal legal research with statutory, case, and conceptual approaches. The findings show that online gambling regulation is constructed through the National Criminal Code, the ITE Law, the State Civil Apparatus Law, regulations on electronic systems and private electronic system providers, and the Money Laundering Law. State officials may be held criminally liable when abuse of authority is proven through intent, contribution to the continued accessibility of gambling sites, receipt of benefits, participation, assistance, or concealment of gambling proceeds. The formulated model combines access-based supervision, audit trails, digital records, periodic site verification, electronic evidence, role-based liability, and follow-the-money investigation. The novelty lies in linking public authority, digital access control, mens rea, role-based participation, economic benefit, and criminal enforcement within one integrated framework.